2023
DOI: 10.3389/fgene.2023.996362
|View full text |Cite
|
Sign up to set email alerts
|

High GTSE1 expression promotes cell proliferation, metastasis and cisplatin resistance in ccRCC and is associated with immune infiltrates and poor prognosis

Abstract: Background: Clear cell renal cell carcinoma is the most common and fatal form of kidney cancer, accounting for 80% of new cases. Although it has been reported that GTSE1 is highly expressed in a variety of tumors and associated with malignant progression and poor clinical prognosis, its clinical significance, correlations with immune cell infiltration and biological function in ccRCC are still poorly understood.Methods: The gene expression, clinicopathological features, and clinical significance of GTSE1 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
1
6
1
Order By: Relevance
“…Knock-down results showed that downregulation of GTSE1 suppressed proliferation, mobility, invasion and angiogenesis of NPC cells, and also inhibited the tumor growth in the NPC xenografted mice. Similar results was observed that silencing of GTSE1 represses cell proliferation, mobility and invasion have been reported in non-small-cell lung cancer cells [ 21 ], clear cell renal cell carcinoma [ 19 , 20 ], esophageal squamous cell carcinoma [ 27 ], colon cancer [ 32 ], bladder cancer [ 14 ], acral melanoma [ 15 ], and hepatocellular carcinoma [ 17 ]. Collectively, knockdown of GTSE1 attenuated growth, mobility, invasion and angiogenesis of NPC cells.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Knock-down results showed that downregulation of GTSE1 suppressed proliferation, mobility, invasion and angiogenesis of NPC cells, and also inhibited the tumor growth in the NPC xenografted mice. Similar results was observed that silencing of GTSE1 represses cell proliferation, mobility and invasion have been reported in non-small-cell lung cancer cells [ 21 ], clear cell renal cell carcinoma [ 19 , 20 ], esophageal squamous cell carcinoma [ 27 ], colon cancer [ 32 ], bladder cancer [ 14 ], acral melanoma [ 15 ], and hepatocellular carcinoma [ 17 ]. Collectively, knockdown of GTSE1 attenuated growth, mobility, invasion and angiogenesis of NPC cells.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, GTSE1 has been revealed to be closely related to the process of different tumors. GTSE1 has been revealed as a biomarker for the immunosuppressive tumor microenvironment based on a pan-cancer analyses [ 13 ], and high expression of GTSE1 is associated with poor patient survival in many cancer types, such as bladder cancer [ 14 ], acral melanoma [ 15 ], hepatocellular carcinoma [ 16 , 17 ], lung cancer [ 18 ], clear cell renal cell carcinoma [ 19 , 20 ], non-small-cell lung cancer [ 21 ], cervical cancer [ 22 ], and breast cancer [ 23 ]. Moreover, GTSE1 is identified to participate in the proliferation, migration, and invasion of bladder cancer [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a high GTSE1 expression level was linked to the decreased overall/disease‐specific survival. Lei et al 29 developed a predictive model for clear cell renal cell carcinoma (ccRCC) patients, utilizing age, gender, and GTSE1 expression level, to estimate survival probabilities at 1, 3, and 5 years. They found that increased GTSE1 expression was associated with lower prognostic survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have explored the link of GTSE1 and immune‐related cells, particularly in the context of cancer immunotherapy involving immune checkpoint inhibitors (ICIs). 32 Lei et al 29 discovered a correlation between overexpression of GTSE1 and increased infiltration of immune cells in renal cell carcinoma. Co‐expression analysis revealed a correlation between elevated levels of GTSE1 and the presence of ICIs, including PDCD1 (PD1), LAG3, and CTLA4.…”
Section: Discussionmentioning
confidence: 99%